2020
DOI: 10.5812/iranjradiol.104950
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Low-Dose Chest CT Scan for Initial Triage of COVID-19

Abstract: Background: Chest CT scan is frequently used for diagnosis of coronavirus disease 2019 (COVID-19), especially in regions with limited availability of reverse-transcription polymerase chain reaction test (RT-PCR) test. Low-dose CT of chest offers acceptable image quality with lower radiation dose, particularly important in younger patients. Objectives: We have designed the current study to evaluate the diagnostic efficacy of low-dose chest CT versus early RT-PCR results, for triage of COVID-19 patients. Patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
1
7
1
Order By: Relevance
“…The inter-observer agreement in this study was excellent, similar to Tabatabaei et al [18] and Dangis et al [19]. The accuracy in this study was also high but did not exceed that of Bahrami-Motlagh et al (96.6%) [20]. The CT sensitivity also in this study exceeded that in Azadbakht et al [25] (60-70%).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The inter-observer agreement in this study was excellent, similar to Tabatabaei et al [18] and Dangis et al [19]. The accuracy in this study was also high but did not exceed that of Bahrami-Motlagh et al (96.6%) [20]. The CT sensitivity also in this study exceeded that in Azadbakht et al [25] (60-70%).…”
Section: Discussionsupporting
confidence: 87%
“…These estimated radiation doses are 12.5:13.3 and 18.1:20 times more than that of the low-dose and the ultra-low-dose CT protocols in this study respectively. Additionally, the DLP and absolute cancer risk of the ultra-low-dose CT in this study were lower than those provided by Tabatabaei et al [ 18 ], Dangis et al [ 19 ] and Bahrami-Motlagh et al [ 20 ]. On the other hand, the CTDIvol was higher than that provided by Shiri [ 24 ] (0.7 mGy) who used lower kV (90 kV) and lower pitch (0.8).…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…First, this goal was investigated using a low-dose chest CT approach (< 3 mGy) that has been recommended by some experts [ 20 , 21 ]. The evidence shows that low-dose chest CT had high sensitivity (96.6%) for triage of COVID-19 in a study by Bahrami-Motlagh et al [ 22 ] on 163 patients with suspected COVID-19 where 80 cases had positive RT-PCR results. At the next step, we intended to investigate ultra-low-dose chest CT and determine its sensitivity and specificity for triage purposes.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that CT examinations are mostly used to monitor the severity of disease and less for diagnostic purposes. However, in other reports, it is pointed out that there are still many countries using CT as a diagnostic tool for patients suspected of COVID-19, possibly due to limited resources [21,43]. Homayounieh's main finding was variations in the number of scan phases and CT exams per patient among healthcare facilities across the world.…”
Section: Scanning Considerationsmentioning
confidence: 98%